Genetic diversity in Plasmodium falciparum merozoite surface protein 1 and 2 coding genes and its implications in malaria epidemiology: a review of published studies from 1997–2007 - Kiwanuka, Gertrude N. (Journal of vector borne diseases, 2009)
A major characteristic of human malaria parasites is their genetic diversity and an increasing number of studies have been reported on the epidemiology of Plasmodium falciparum, mainly focusing on the polymorphism of merozoite surface protein (MSP) 1 and 2 genes. A myriad of information on the genetic diversity and multiplicity of P. falciparum infections has been generated from such studies, and a range of molecular tools for epidemiological studies were produced, creating both optimism and pessimism in regard to the global efforts to control malaria. The objective of this review is to provide current and comprehensive information on the diversity in the gene that encodes the merozoite surface protein (MSP) 1 and 2 of P. falciparum and its implications on the epidemiology of malaria, immunity and development of control measures, and point out some research themes that need to be explored further by utilizing molecular techniques currently at our disposal. Articles published in journals between 1997 and 2007 are herein reviewed.
Keywords: Genetic diversity; Immune response; Merozoite surface protein; Multiplicity; Plasmodium falciparum